PROFESIONALISME GURU PAI BERDASARKAN ANALISIS KOMPONEN KURIKULUM 2013 DI ACEH - Basri Ibrahim, Zainal Abidin, Andika Jaya Putra (IAIN Ambon, 2019)
The purpose of this study was to determine the ability of teachers in aspects of learning planning, implementation, and assessment of learning Islamic education in Aceh. The research method used is quantitative survey format. The study population was all PAI teachers in East Aceh District, totaling 62 people. The research sample is the whole population (total sampling). The research instrument used a questionnaire Data analysis using inferential statistical tests (F test) assisted by SPSS version 21.0. The results showed that aspects of PAI teacher planning in East Aceh District had been able to apply the 2013 curriculum in learning. This can be seen from their ability to implement PAI learning using the 5M approach and they are able to conduct authentic assessments well. Therefore, special attention needs to be paid by the Regional Government, especially the Aceh Education Office to improve the professionalism of PAI teachers in Aceh so that the objectives of national education can be achieved optimally.